2006
DOI: 10.1111/j.1600-0722.2006.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium, given before or after a fluoride insult, on hamster secretory amelogenesis in vitro

Abstract: We tested the hypothesis that high-calcium medium given prior to or immediately after exposure to fluoride (F) reduces the negative effects of F on secretory amelogenesis. Hamster molar tooth germs were grown in organ culture in media with different calcium levels. Deposition of enamel matrix and matrix mineralization were monitored by incorporation of [3H]proline and uptake of 45Ca and acid-soluble 32PO4. Ameloblast structure and the occurrence of a fluorotic enamel matrix were examined by light and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
1
11
0
2
Order By: Relevance
“…Amelogenin expression was upregulated by calcium at both the mRNA and protein levels. These results are consistent with those of Bronkers et al, who showed that calcium can, to some extent, rescue amelogenin expression in fluoride-treated tooth organs, and calcium alone can increase amelogenin expression in organ culture (Bronckers et al, 2006). Further studies are required to determine whether calcium acts directly on the amelogenin promoter, or indirectly to enhance amelogenin expression through other signaling pathways.…”
Section: Discussionsupporting
confidence: 94%
“…Amelogenin expression was upregulated by calcium at both the mRNA and protein levels. These results are consistent with those of Bronkers et al, who showed that calcium can, to some extent, rescue amelogenin expression in fluoride-treated tooth organs, and calcium alone can increase amelogenin expression in organ culture (Bronckers et al, 2006). Further studies are required to determine whether calcium acts directly on the amelogenin promoter, or indirectly to enhance amelogenin expression through other signaling pathways.…”
Section: Discussionsupporting
confidence: 94%
“…In control conditions, this expression was weaker than that in odontoblasts, but it was induced by fluoride, especially in the ameloblasts during the maturation stage. Most changes caused by fluoride are related to cell/matrix/mineral interactions, especially during the maturation stage of amelogenesis, precisely when asporin is most strongly expressed. Apatite mineral may locally enhance fluoride concentration due to inorganic fluoride–mineral interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of metalloproteinase is down regulated by fluoride (Zhang et al, 2006), and its activity is reduced, because the free Ca ++ concentration in fluoroapatite is lowered (Aoba and Fejerskov, 2002). Metalloproteinase-20 was less active after fluoride administration in vivo (DenBesten et al, 2002), and excess calcium in organ culture partially prevented formation of fluorotic enamel (Bronckers et al, 2006). Furthermore, also the activity of enzymes may be directly affected by fluoride, as observed for carbonic anhydrase (Innocenti et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…Proteoglycans were altered in their glycosaminoglycan side chains (Waddington and Langley, 1998), resulting in a hampered extraction from fluoride-treated tooth slices (Waddington et al, 2004). In forming enamel, elevated fluoride concentrations lead to a higher protein content with consequences for mineral crystal growth (Robinson et al, 2004;Bronckers et al, 2006;Bartlett et al, 2005). Inhibition of proteolysis may account for inefficient protein removal (Aoba and Fejerskov, 2002;DenBesten et al, 2002).…”
Section: Introductionmentioning
confidence: 98%